An ecological measure of rapid and automatic face-sex categorization. (June 2020) - Rekow, Diane; Baudouin, Jean-Yves; Rossion, Bruno; Leleu, Arnaud
Abstract: Sex categorization is essential for mate choice and social interactions in many animal species. In humans, sex categorization is readily performed from the face. However, clear neural markers of face-sex categorization, i.e., common responses to widely variable individuals from one sex, have not been identified so far in humans. To isolate a direct signature of rapid and automatic face-sex categorization generalized across a wide range of variable exemplars, we recorded scalp electroencephalogram (EEG) from 32 participants (16 females) while they were exposed to variable natural face images from one sex alternating at a rapid rate of 6 Hz (i.e., 6 images per second). Images from the other sex were inserted every 6th stimulus (i.e., at a 1-Hz rate). A robust categorization response to both sex contrasts emerged at 1 Hz and harmonics in the EEG frequency spectrum over the occipito-temporal cortex of most participants. The response was larger for female faces presented among male faces than the reverse, suggesting that the two sex categories are not equally homogenous. This asymmetrical response pattern disappeared for upside-down faces, ruling out the contribution of low-level physical variability across images. Overall, these observations demonstrate that sex categorization occurs automatically after a single glance at natural face images and can be objectively isolated and quantified in the human brain within a few minutes.